The Impact of Podcast Video Creation on Students' Speaking Proficiency in Project-Based Learning - Safar, Muhammad; Masruddin; St. Hartina (EDUTREND: Journal of Emerging Issues and Trends in Education, 2025)
This study aimed to explore the effectiveness of podcast video creation as a Project-Based Learning (PBL) approach to enhance students' speaking abilities in secondary education. The research was motivated by low speaking proficiency among students, influenced by factors such as lack of confidence, limited vocabulary, and insufficient practice opportunities. Using a pre-experimental design, the study involved 28 eleventh-grade students selected through cluster random sampling. Pre-tests and post-tests were conducted to measure improvements in speaking skills, with data analyzed using SPSS (paired t-test). Results showed a significant improvement in students' speaking abilities, with post-test scores (M = 51.5) higher than pre-test scores (M = 42.4), and a t-value of 11.145 (p < 0.05). The findings highlight that PBL through podcast video creation positively impacts accuracy, fluency, and comprehensibility in speaking. This study underscores the practical implications of integrating technology into education, fostering student engagement, collaboration, and enhanced language proficiency. Future research is encouraged to incorporate control groups and explore the effects of this approach on other language skills.